On the mechanism of chaperone activity of the small heat-shock protein of Methanococcus jannaschii - Kim, Rosalind (National Academy of Sciences, 2003)
The small heat-shock protein (sHSP) from Methanococcus jannaschii (Mj HSP16.5) forms a homomeric complex of 24 subunits and has an overall structure of a multiwindowed hollow sphere with an external diameter of ≈120 Å and an internal diameter of ≈65 Å with six square “windows” of ≈17 Å across and eight triangular windows of ≈30 Å across. This sHSP has been known to protect other proteins from thermal denaturation. Using purified single-chain monellin as a substrate and a series of methods such as protease digestion, antibody binding, and electron microscopy, we show that the substrates bind to Mj HSP16.5 at a high temperature (80°C) on the outside surface of the sphere and are prevented from forming insoluble substrate aggregates in vitro. Circular dichroism studies suggest that a very small, if any, conformational change occurs in sHSP even at 80°C, but substantial conformational changes of the substrate are required for complex formation at 80°C. Furthermore, deletion mutation studies of Mj HSP16.5 suggest that the N-terminal region of the protein has no structural role but may play an important kinetic role in the assembly of the sphere by “preassembly condensation” of multiple monomers before final assembly of the sphere.